2010
DOI: 10.1542/peds.2008-3429
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Children Enrolled in Pediatric Oncology Research: Implications for Assent

Abstract: BACKGROUND: Most children with cancer enroll in clinical research trials. Whenever possible, children must provide their assent before enrolling in research studies. We studied what children aged 7 to 18 with cancer understand about research, their research-related treatment, and their preferences for inclusion in decision-making. PROCEDURE: Thirty-seven face-to-face, audiorecorded interviews using a novel, semi-structured to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 40 publications
(44 reference statements)
5
77
0
Order By: Relevance
“…This therapeutic misconception was prevalent in the population of children younger than 13 y, but not in late adolescents. In adults, therapeutic misconception emerged as a major theme (16); in previous studies in children, it was prevalent as well (13). Thus, in children, understanding of the purpose of clinical research relies heavily on the provision of information, which should be tailored to their comprehension level (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This therapeutic misconception was prevalent in the population of children younger than 13 y, but not in late adolescents. In adults, therapeutic misconception emerged as a major theme (16); in previous studies in children, it was prevalent as well (13). Thus, in children, understanding of the purpose of clinical research relies heavily on the provision of information, which should be tailored to their comprehension level (17).…”
Section: Discussionmentioning
confidence: 99%
“…Providing participants with inadequate information concerning the particulars of the research also interferes with the participants' ability to make well-considered decisions (10). Studies in adolescents, one of which concerned a hypothetical research project, demonstrated that several participants expected direct health benefit from being questioned and examined by the physician (11)(12)(13). A main reason for participation was charity (14), and half of the eligible subjects refused for no apparent reason (15).…”
mentioning
confidence: 99%
“…29 Research examining knowledge about clinical trials among children and adolescents has delineated a lack of understanding of what clinical trials are, the difference between clinical versus nonclinical research treatments, and incorrect assumptions about the level of invasiveness of clinical trial interventions compared with standard treatments. 30,31 Misinformation and a lack of awareness may also be the result of poor readability, understandability, and clarity of consent forms used in child and adolescent cancer research and clinical trials. 32,33 A medical provider' s knowledge of available clinical trials and communication about clinical trial information can also affect an adolescent' s awareness level.…”
Section: Information Knowledge and Awareness About Clinical Trialsmentioning
confidence: 99%
“…30 The importance of speaking directly to the child or adolescent, instead of solely to the parent, was also reported. Children and adolescents aged 7 to 18 years in the same study also reported that speaking to other children and adolescents who are already enrolled in clinical trials would be helpful during the decision-making and consenting process.…”
Section: Issues Concerning Clinical Trial Consenting Processmentioning
confidence: 99%
“…It should be noted however that, in comparison to adults, children's understanding of their specific health conditions, of the global concept of illness and of medical research is more basic and improves with maturation [18,23]. Specifically, the concept of treatment alternatives, the duration of participation, the right to withdraw and the voluntary nature of participation seem to be difficult to understand [23,24] even if the potential participants were adolescents [25].…”
Section: Children's Comprehensionmentioning
confidence: 99%